Swimming Improves Memory Function and Decreases N-Methyl-D-Aspartate in Ageing Rats - Hanik Badriyah Hidayati; Purwo Sri Rejeki; Lilik Herawati; Susi Wahyuning Asih; Suhartati Suhartati; Siti Khaerunnisa (Institute of Medico-legal Publications Pvt Ltd, 2021)
A single Memory impairment substantially reduces the quality of life in the elderly. It is associated with thealteration of neurotrophic (NT) factors, such as brain-derived neurotrophic factor (BDNF) and glutamatereceptor N-methyl-D-aspartate (NMDA). Exercise is often used to reduce cognitive impairment. Previousstudies show that the benefits of aerobic exercises on such impairments are correlated with increasing BDNFand preventing the production of NMDA. However, some results remain controversial. Thus, the associationbetween exercise and Memory was addressed by examining increases in BDNF and the reduction of NMDAin ageing rats. The study used a randomized, post-test-only controlled group of 30 male one-year-old ageingRattus norvegicus divided into three groups, namely, K0 (control) and K1 and K2 (aerobic swimmingexercise). K1 and K2 animals differed in the frequency of exercise, which is three and four sessions perweek, respectively. Memory was assessed using Y-maze performance. BDNF and NMDA were analyzedusing enzyme-linked immunosorbent assays. A significant improvement in memory function and reductionin the NMDA level were observed in K1 and K2 group rats (p = 0.001; p = 0.041). No significant impact onthe BDNF levels was observed (p = 0.387). Swimming may boost Memory by reducing the NMDA levelbut not by increasing BDNF. Swimming is a promising method for preventing or delaying memory loss indegenerative brain diseases. Further investigation is needed to fully understand underlying mechanisms.